1996
DOI: 10.1111/j.1365-2648.1996.tb03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Social support and its impact on mothers’experiences of childbirth

Abstract: The purpose of this study was to look at the networks of social support available for mothers during pregnancy and childbirth. Another concern was to describe mothers' experiences of labour and the connections of social support with those experiences. The data were collected through the use of two questionnaires submitted to 200 mothers recruited from Tampere University Hospital. Both instruments--Norbeck's Social Support Questionnaire and a scale designed by the author--were based on Kahn's (1979) theory of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 9 publications
2
83
0
2
Order By: Relevance
“…Surveys such as the Postpartum Depression Predictors Inventory (PPDI) [1] reflect meta-analyses of risk factors for PPD [2], including lack of social support, socioeconomic status, and infant temperament, among others (see [30] for more on risks and influencers of PPD). Lack of social support and social isolation in particular, along with psychological stress have been shown to influence the attitudes, emotions, and behaviors of new mothers [10,48]. In another study [46], Scott et al found that the strongest predictors of PPD were past history of psychopathology and psychological disturbance during pregnancy, poor marital relationship, low social support, and stressful life events.…”
Section: Clinical/psychiatry Literature On Ppdmentioning
confidence: 98%
See 1 more Smart Citation
“…Surveys such as the Postpartum Depression Predictors Inventory (PPDI) [1] reflect meta-analyses of risk factors for PPD [2], including lack of social support, socioeconomic status, and infant temperament, among others (see [30] for more on risks and influencers of PPD). Lack of social support and social isolation in particular, along with psychological stress have been shown to influence the attitudes, emotions, and behaviors of new mothers [10,48]. In another study [46], Scott et al found that the strongest predictors of PPD were past history of psychopathology and psychological disturbance during pregnancy, poor marital relationship, low social support, and stressful life events.…”
Section: Clinical/psychiatry Literature On Ppdmentioning
confidence: 98%
“…Beyond PPD, researchers have been increasingly interested in understanding how social media activities can be used to infer the wellbeing of people, and conditions and symptoms related to diseases [36] and disease contagion, e.g., flu [48]. Facebook use has been shown to help those with lower selfesteem to attain higher social capital [47].…”
Section: Social Media/network In Health and Wellnessmentioning
confidence: 99%
“…In Tarkka and Paunonen's (1996) study, the researchers reported that women in labor seek social support from their midwife or other caregiver. This type of continuous support was described by Hodnett and colleagues (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Another study, conducted by researchers in Finland, sought to determine specifically where pregnant Finnish women derive their forms of social support during pregnancy, labor, and birth (Tarkka & Paunonen, 1996). The researchers defined social support as ''.intentional human interactions that involve one or more of the following elements: affect., affirmation., and/or aid'' (p. 71).…”
Section: Social Supportmentioning
confidence: 99%
“…Further studies have demonstrated that satisfaction with the social support given by a woman's partner and/or family had significant beneficial effects on the later well-being of the mother and child by reducing the risk of postpartum depression [80,81] . Collins, Dunkel-Schetter [82] found social support resources during pregnancy had a substantial, statistically significant correlation between prenatal support quality and depressed mood.…”
Section: Social Factors Associated With Perinatal Healthmentioning
confidence: 99%